2021
DOI: 10.3233/ch-201082
|View full text |Cite
|
Sign up to set email alerts
|

Can erythrocytes behavior in microcirculation help the understanding the physiopathology and improve prevention and treatment for covid-19?

Abstract: Low plasma estrogens, vitamin D deficiency, obesity, diabetes, cardiovascular diseases, thromboembolism, and impaired microcirculation are linked to the severity of covid-19. Studies have suggested that these comorbidities also are related to erythrocyte factors linked to increased blood viscosity in microcirculation such as erythrocyte aggregation and erythrocyte deformability. Increased blood viscosity in microcirculation can lead to a decrease in oxygenation and nutrition of tissues. Therefore erythrocyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Hyperviscosity disrupts the Fåhræus-Lindqvist effect and could result in the formation of in-situ capillary thrombosis. Hyperviscosity in microcirculation can also impair the delivery of oxygen and nutrients to the tissues [38] . In a study of 15 severe COVID-19 patients, it is observed that all patients had high values for plasma viscosity ranging from 1.9–4.2 cP (normal range 1.4–1.8 cP) [39] .…”
Section: Overview Of the Pathophysiology Of Thrombosismentioning
confidence: 99%
“…Hyperviscosity disrupts the Fåhræus-Lindqvist effect and could result in the formation of in-situ capillary thrombosis. Hyperviscosity in microcirculation can also impair the delivery of oxygen and nutrients to the tissues [38] . In a study of 15 severe COVID-19 patients, it is observed that all patients had high values for plasma viscosity ranging from 1.9–4.2 cP (normal range 1.4–1.8 cP) [39] .…”
Section: Overview Of the Pathophysiology Of Thrombosismentioning
confidence: 99%
“…The recent COVID-19 pandemic has generated a host of studies in all areas of biomedical research [235], and, unsurprisingly, disturbances in microcirculation [236] and the rheologic properties of blood [237] have been described. It is clear that endotheliopathies are important clinical features of acute COVID-19 [238,239].…”
Section: Covid-19mentioning
confidence: 99%
“…In addition, it has been associated with inflammatory and vascular endothelial function indices [6]. In the context of COVID-19, changes in erythrocyte function and microcirculation have been considered as an important part of the pathophysiology of the disease and need to be deeply investigated in order new effective treatments to emerge [7][8][9]. Along this line, red blood cell rheological properties are found to be impaired in COVID-19 [10,11].…”
Section: Covidmentioning
confidence: 99%